Complementary and Integrative Management of Pediatric Lower Urinary Tract Dysfunction Implemented within an Interprofessional Clinic - Kathryn E. Morgan; Susan V. Leroy; Sean T. Corbett; Jaclyn A. Shepard (MDPI AG, 2019)
Lower urinary tract dysfunction in children is a common multifactorial functional problem that often correlates with bowel dysfunction and behavioral disorders. Ideal management combines integrative therapies that optimize bladder and bowel habits, address behavioral issues, foster mind−body connection, and improve pelvic floor muscle dysfunction. Movement therapies that teach diaphragmatic breathing and relaxation, mind−body awareness, and healthy pelvic floor muscle function are vital for long-term symptom improvement in children. This paper outlines recommendations for integrative management of these patients and discusses a recently developed interprofessional clinic that aims to better meet these patients’ complex needs and to provide patients with an integrated holistic plan of care. Additional work is needed to scientifically assess these treatment models and educate providers across the various disciplines that evaluate and treat these patients.